2022
DOI: 10.1016/j.aucc.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a hospital-wide multidisciplinary blunt chest injury care bundle (ChIP): Fidelity of delivery evaluation

Abstract: Please cite this article as: Kourouche S et al., Implementation of a hospital-wide multidisciplinary blunt chest injury care bundle (ChIP): Fidelity of delivery evaluation, Australian Critical Care,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“… b % loss in VTM sensitivity = % sensitivity in SSTM − % sensitivity in VTM. c Z test for comparison of sensitivities between VTM versus SSTM using online tool https://epitools.ausvet.com.au/ztesttwo ( 26 , 27 ). d sensitivity % = [true positive/(true positive + false negative)] × 100.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… b % loss in VTM sensitivity = % sensitivity in SSTM − % sensitivity in VTM. c Z test for comparison of sensitivities between VTM versus SSTM using online tool https://epitools.ausvet.com.au/ztesttwo ( 26 , 27 ). d sensitivity % = [true positive/(true positive + false negative)] × 100.…”
Section: Resultsmentioning
confidence: 99%
“… c Z test for comparison of sensitivities between VTM versus SSTM using online tool https://epitools.ausvet.com.au/ztesttwo ( 26 , 27 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this variation include differences in pathways focusing on ICU escalation or admission criteria, [2][3][4][5] analgesia and pain assessment, [3][4][5][6][7] and respiratory care and assessment. [3][4][5][6] The heterogeneity of the intervention content and purpose has overall limited the ability to integrate findings and make inference. As identified in a previous review, this limitation was further demonstrated through the variation in patient outcomes used to evaluate the impact of these pathways.…”
Section: Commentsmentioning
confidence: 99%
“…This is in the manuscript preparation stage. The fidelity of delivery has been evaluated separately [19]. The treatments within the protocol are all evidence-based and reflect other existing pathways that have been demonstrated to be effective [20].…”
Section: Introductionmentioning
confidence: 99%